2004
DOI: 10.1016/j.phr.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The California Health Interview Survey 2001: Translation of a Major Survey for California's Multiethnic Population

Abstract: The cultural and linguistic diversity of the U.S. population presents challenges to the design and implementation of population-based surveys that serve to inform public policies. Information derived from such surveys may be less than representative if groups with limited or no English language skills are not included. The California Health Interview Survey (CHIS), first administered in 2001, is a population-based health survey of more than 55,000 California households. This article describes the process that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 21 publications
0
90
0
Order By: Relevance
“…It was conducted in English, as well as in a number of other languages, including Spanish, Chinese, Vietnamese, Korean, and Khmer. 22 The overall response rate was estimated as 37.7%, based on the screener completion rate and the extended interview completion rate. 23 The representativeness of CHIS2001 data were evident by the fact that its demographic characteristics were very similar to that of the 2000 US Census, and its health characteristics and behaviors were also very similar to a comparable random-digit dial telephone survey in California, the California Behavioral Risk Factor Surveillance System.…”
Section: Datamentioning
confidence: 99%
“…It was conducted in English, as well as in a number of other languages, including Spanish, Chinese, Vietnamese, Korean, and Khmer. 22 The overall response rate was estimated as 37.7%, based on the screener completion rate and the extended interview completion rate. 23 The representativeness of CHIS2001 data were evident by the fact that its demographic characteristics were very similar to that of the 2000 US Census, and its health characteristics and behaviors were also very similar to a comparable random-digit dial telephone survey in California, the California Behavioral Risk Factor Surveillance System.…”
Section: Datamentioning
confidence: 99%
“…Rather, survey translation is a complex endeavor requiring the development and implementation of a number of careful practices (Brislin, 1970;Census Bureau, 2004;Harkness & Schoua-Glusberg, 1998;Harkness, Van de Vijver & Mohler, 2003;McKay, et al, 1996;Ponce, et al, 2004). Most vexing are the severe challenges to creating survey questionnaires that exhibit the key characteristic of cross-cultural comparability of results (Miller, 2004;Pan & de la Puente, 2005;Schmidt & Bullinger, 2003;Singelis, et al, 2006;Yu, Lee, & Woo, 2004).…”
Section: Challenges To Translation and Establishment Of Cross-culturamentioning
confidence: 99%
“…The original and back-translated versions are compared, and discrepancies noted and reconciled. However, recent reviews by survey researchers and linguists have concluded (as did Brislin's original article) that back-translation should not be regarded as a singular "best practice" (Ponce, et al, 2004) 4 . In particular, a tendency towards over-reliance on word-for-word, literal translations may sacrifice the overall intent of the translated item (Carlson, 2000;Census Bureau, 2004;European Social Survey, 2002;Forsyth, Kudela, Levin, Lawrence, & Willis, 2007;Harkness, et al, 2003;Harkness & Schoua-Glusberg, 1998;Ponce, et al, 2004) 5 .…”
Section: Challenges To Translation and Establishment Of Cross-culturamentioning
confidence: 99%
See 1 more Smart Citation
“…It is the largest state health survey ever conducted and one of the largest health surveys in the nation. CHIS collects extensive information on health-related conditions and behaviors, including smoking behavior (11,12). Utilizing the CHIS public use data, we explored smoking prevalence in California from 2001 to 2012 using a finer 4-level geographic classification derived from ZIP codes of respondents' place of residence (13).…”
Section: Introductionmentioning
confidence: 99%